2020
DOI: 10.1007/s10143-020-01438-5
|View full text |Cite
|
Sign up to set email alerts
|

Escalation therapy in severe traumatic brain injury: how long is intracranial pressure monitoring necessary?

Abstract: Traumatic brain injury frequently causes an elevation of intracranial pressure (ICP) that could lead to reduction of cerebral perfusion pressure and cause brain ischemia. Invasive ICP monitoring is recommended by international guidelines, in order to reduce the incidence of secondary brain injury; although rare, the complications related to ICP probes could be dependent on the duration of monitoring. The aim of this manuscript is to clarify the appropriate timing for removal and management of invasive ICP moni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 69 publications
1
7
0
Order By: Relevance
“…Moreover, studies show that the implementation of evidence-based TBI treatment algorithms are associated with improved outcomes, highlighting the importance of future precise ICP-based guidelines in order to reduce practice disparity among TBI patients [ 39 ]. A low percentage (3.4%) of ICP monitoring-related hemorrhagic complications was found in the present study, similar to the published literature [ 34 , 40 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, studies show that the implementation of evidence-based TBI treatment algorithms are associated with improved outcomes, highlighting the importance of future precise ICP-based guidelines in order to reduce practice disparity among TBI patients [ 39 ]. A low percentage (3.4%) of ICP monitoring-related hemorrhagic complications was found in the present study, similar to the published literature [ 34 , 40 ].…”
Section: Discussionsupporting
confidence: 92%
“…Even though extensive literature has recently been published, the potential benefit of invasive ICP monitoring still remains controversial, despite high percentages of IC-HTN in pediatric sTBI cases, or the generally accepted association between IC-HTN and worse neurologic outcomes [ 3 , 34 ]. The present study evaluated the influences of IC-HTN on the outcome of sTBI pediatric patients, and reports a high percentage of nearly 66% of children who were managed through ICP-guided protocols.…”
Section: Discussionmentioning
confidence: 99%
“…Tiers -one to -three- includes the interventions suggested only in the case of HICP. Goals of tier 1 include CPP maintenance between 60-70 mmHg and partial pressure of carbon dioxide (PaCO 2 ) between 35 and 38 mmHg, eventually implementing analgesia and sedation, using an intermittent bolus of osmotic agents, placing external ventricular drainage to allow cerebrospinal fluid drainage [ 24 ], and implementing electroencephalographic monitoring and prophylactic anticonvulsants if the risk of seizures is deemed high [ 2 , 21 - 23 ]. Tier 2 is expected to implement tier 1 interventions as much as mild hypocapnia (32-35 mmHg), neuromuscular paralysis, inotropes or vasopressors to assess if cerebral autoregulation is intact.…”
Section: Current Therapies For Tbimentioning
confidence: 99%
“…It has been reported that one of the main determinants of poor outcome in patients with sTBI is an increased intracranial pressure (ICP), which can result from intracranial hemorrhage, brain edema, and obstructive hydrocephalus, among others. 1) Therefore, several interventions to control ICP and improve the outcome, including management of body temperature and barbiturate therapy, have been widely studied. 2) Barbiturates exert sedative and anesthetic effects by potentiating the action of γ-aminobutyric acid (GABA) at the GABA A receptor.…”
Section: Introductionmentioning
confidence: 99%